(untitled) (Моделювання, керування та інформаційні технології, 2019)
Triangular norms and associative functions are base of connectives in fuzzy logic and fuzzy systems. New connective operator that can generate different classes of fuzzy connectives is proposed. It is proved that this operator satisfies the requirements of such axioms as commutativity, associativity, monotonicity and boundary conditions. It is parameterized and therefore new triangular norms are obtained. Constructed parameterized triangular norms are of a strict and Archimedian type.